Ethnomusicological Perspectives on Gaomi Miaoqiang: Unveiling the Cultural Tapestry - Tan, Xuyao (Pacific International Journal, 2024)
This ethnomusicological study delves into the vibrant tapestry of Gaomi Miaoqiang, a traditional Chinese folk opera hailing from the Shandong province, exploring its historical evolution, linguistic intricacies, musical characteristics, and cultural implications. With a foundation rooted in the "肘鼓子" (Zhou Guzi) series of Shandong local operas, Gaomi Miaoqiang has evolved over centuries, blending folk singing styles and incorporating influences from Huagu yangge and Lüqin opera. Acknowledged as China’s 67th National Intangible Cultural Heritage, Gaomi Miaoqiang represents a profound cultural legacy.The study scrutinizes the language features of Gaomi Miaoqiang, emphasizing simplicity, clarity, and the integration of local dialects, reflecting the rural life of the Gaomi community. Musical analysis unveils the operatic singing styles, instrumental accompaniment, and the evolution of musical composition. From the authentic tones of the "Original Board" to the intricate patterns of the "Dayoutou Board," Gaomi Miaoqiang’s musical journey embodies emotional depth and narrative complexity. The study also explores the roles, makeup, costumes, and stage art, highlighting the art form’s transition from grassroots performances to professional troupes. Furthermore, Gaomi Miaoqiang’s cultural significance is illuminated, portraying its role as a conduit for spiritual solace and emotional release within local communities. Recognizing its enduring influence, the study advocates for the preservation of Gaomi Miaoqiang’s distinctiveness amid urban influences. As Gaomi Miaoqiang navigates the intersection of tradition and modernity, it emerges as a cultural beacon, casting light on the rich legacy of Chinese folk opera and emphasizing the critical role of ethnomusicology in unraveling the intricate threads of cultural heritage.